Refinements of Generalized Aczél's Inequality and Bellman's Inequality and Their Applications - Jing-Feng Tian; Shu-Yan Wang (Journal of Applied Mathematics)
We give some refinements of generalized Aczél's inequality and Bellman's inequality proposed by Tian. As applications, some refinements of integral type of generalized Aczél's inequality and Bellman's inequality are given.